PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS III SDN SAWUNGGALING DENGAN MEDIA AJAR KOTAK RAHASIA - PURWITASARI, ERVINA DWI; HAPSARI, KARTIKA AYU; MARDHIYAH, SITI MARVUATIL; NGAZIZAH , NUR (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This research is motivated by the low results of student activity and learning on Pancasila material in class III SDN Sawunggaling. One solution to overcome this problem is to apply the secret box media (Mystery Box). The objectives of this research include 1) Knowing how the application of secret box teaching media can improve the activity and learning outcomes of class III SDN Sawunggaling students. 2) Knowing how to increase the activity and learning outcomes of class III SDN Sawunggaling students through the application of secret box teaching media. This study uses a classroom action research (CAR) approach implemented in two cycles. Each cycle includes two meetings with four stages, namely planning, implementation, observation, and reflection. The research subjects consisted of 10 grade III students. Data collection techniques are in the form of documentation, observation, and tests. Based on the results of data analysis, it can be seen that after the action in cycles I and II, there was an increase in student activity and learning outcomes. In the pre-action activities, an increase in student activity was obtained, the results in the pre-cycle, the percentage of student activity reached 40%, while in cycle I it increased to 55.56% with a sufficient category, then in cycle II it increased again to 88.89% with a high category. And the learning outcomes in the pre-action initially reached 30% completeness, in cycle I it reached 70%, and in cycle II it increased to 90%. So it can be concluded that the implementation of the secret box teaching media can increase the activity and learning outcomes of grade III students of SDN Sawunggaling. ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya hasil keaktifan dan belajar siswa pada materi Pancasila di kelas III SDN Sawunggaling. Salah satu solusi untuk mengatasi masalah ini adalah dengan menerapkan media ajar kotak rahasia (Mistery Box). Tujuan penelitin ini diantaranya 1) Mengetahui bagaimana penerapan media ajar kotak rahasia dapat meningkatkan keaktifan dan hasil belajar siswa kelas III SDN Sawunggaling. 2) Mengetahui bagaimana peningkatan keaktifan dan hasil belajar siswa kelas III SDN Sawunggaling melalui penerapan media ajar kotak rahasia. Penelitian ini menggunakan pendekatan penelitian tindakan kelas (PTK) yang dilaksanakan dalam dua siklus. Tiap siklus mencakup dua pertemuan dengan empat tahapan, yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian terdiri dari 10 siswa kelas III. Teknik pengumpulan data berupa dokumentasi, observasi, dan tes. Berdasarkan hasil analisis data dapat diketahui bahwa setelah tindakan pada siklus I dan II, terjadi peningkatan hasil keaktifan dan belajar siswa. Pada kegiatan pra tindakan diperoleh peningkatan keaktifan siswa didapatkan hasil pada pra siklus, presentase keaktifan siswa mencapai 40%, sedangkan pada siklus I meningkat menjadi 55,56% dengan kategori cukup, kemudian pada siklus II meningkat lagi menjadi 88,89% dengan kategori tinggi. Serta hasil belajar pada pra tindakan awalnya mencapai ketuntasan sebesar 30%, pada siklus I mencapai 70%, dan pada siklus II meningkat menjadi 90%. Maka dapat disimpulkan implementasi media ajar kotak rahasia dapat meningkatkan keaktifan dan hasil belajar siswa kelas III SDN Sawunggaling.